Forecasting advertising and media effects on sales: Econometrics and alternatives. (November 2018) - Dawes, John; Kennedy, Rachel; Green, Kesten; Sharp, Byron
The contribution of regression analysis (econometrics) to advertising and media decision-making is questioned and found wanting. Econometrics cannot be expected to estimate valid and reliable forecasting models unless it is based on extensive experimental data on important variables, across varied conditions. This article canvasses alternative, evidence-based methods that have been shown to be useful for forecasting problems. These methods are described with the hope that they are more widely used for marketing forecasting. The approaches include media and copy experiments, analyses of individual level single source data, and structured expert judgment.